KURIKULUM NASIONAL DAN KURIKULUM INTERNASIONAL DALAM MENINGKATKAN DAYA SAING SISWA - Samsuardi Samsuardi; Abdul Hadi (Jurnal Pendidikan Nusantara, 2026)
The curriculum is a strategic instrument in shaping students’ competencies, character and competitiveness amidst global dynamics. This article aims to analyse the role of the national curriculum and the international curriculum in enhancing students’ competitiveness, as well as to identify the strengths, challenges and opportunities for integrating the two within the education system. This study employs a qualitative approach using a literature review method, analysing various relevant literature on national and international curricula. The findings indicate that the national curriculum has strengths in instilling national values, alignment with the socio-cultural context, and the standardisation of educational standards. Meanwhile, the international curriculum tends to place greater emphasis on critical thinking, creativity, communication, collaboration, and readiness to face global competition. Both types of curriculum make a significant contribution to the development of student competitiveness, albeit with different orientations and emphases.The conclusion of this study affirms that the enhancement of student competitiveness will be more optimal if the education system is able to integrate the strengths of the national and international curricula in a balanced manner. Such integration can be achieved through competence-based learning, the strengthening of global literacy, and the preservation of national identity as the foundation of students’ character.